Expert PHP and MySQL : application design and development - Rochkind, Marc (Apress Imprint: Apress, 2013)
Expert PHP and MySQL takes you beyond learning syntax to showing you how to apply proven software development methods to building commerce-grade PHP and MySQL projects that will stand the test of time and reliably deliver on customer needs. Developers of real-world applications face numerous problems that seem trivial on the surface, but really do take some skill to get right. Error handling is about more than just the mechanics in the PHP syntax, but also about handling MySQL errors, logging those errors, and about hiding information about application internals that error messages sometimes can expose. Meet these challenges and more head-on! Author Marc Rochkind shows how to begin a project right, with a clear contract and set of written requirements. You'll learn about project organization, setting up a solid development environment, connecting with client personnel.  Database design is essential, and Expert PHP and MySQL has you covered with guidance on creating a sound model and database, and on pushing functionality into the database as appropriate; not everything should be done in PHP. Error handling is covered at both the PHP and MySQL levels. Application structure is covered. Guidance is provided on reporting. And finally there is conversion. In Expert PHP and MySQL you'll explore the following:  The popular and widely used combination of PHP and MySQL Commercial-grade application of language and database features Human factors such as planning and organization Organizing a project to meet requirements and satisfy the customer Structuring an application for efficient development and future modification Coding PHP for productivity, reliability, security Generating online, downloadable, and printed reports Converting existing data to the new application